ETNOGRAFI KOMUNIKASI TRADISI TOLAK BALA MENYIEE SUKU MELAYU PETALANGAN DESA PANGKALAN BUNUT KECAMATAN BUNUT KABUPATEN PELALAWAN PROVINSI RIAU - Septyani Adiyan Putri; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Seven monthly is one tradition carried to invoke the protection when the baby in the womb up to the birth. Seven Monthly tradition among Malays Petalangan Pelalawan known as Menyiee. Menyiee is a tradition carried to pray for someone who was pregnant at the age of seven months of pregnancy, to pray for the baby is still in the womb, to stay healthy and also to know the state or position of the baby in the womb. The purpose of this study was to determine how the situations, events, and acts of communication in the tradition of the Malay ethnic menyiee Petalangan in the village of Pangkalan Bunut Bunut Pelalawan District of Riau Province.This type of researchaaaaaasez is qualitative ethnographic approach to communication. Data collected through observation and interviews. Informants were obtained as many as 6 people consisting of two people's status as host of the show seven months and four people are village officials and people who know and understand the events menyiee. Data collection techniques by using purposive. After the interviews, participant observation, and documentation.The results obtained showed that the communicative situation in the event menyiee done at home alone, or at home, the parents of the male or female and was attended by parents, neighbors, relatives, and community members Pangkalan Bunut. Communicative events by Hymes: type of event that is greeting the candidate's grandfather, a topic which is seven monthly performed for the first child, the purpose and function of prayer to implore survived, namely setting menyiee event held in the afternoon at about 13:30 pm until finished, participants are relatives, neighbors and family, form a message that the sanctity, the content of the message that is for safety and convenience, the action sequences are Mawlid al-Barzanjī, swing slap, examination by midwives, the rules of interaction that is inviting the community, the norms of interpretation are appreciated and cultural values. While in communicative acts in the form of people who know and understand the implementation menyiee event that the host inmenyiee.